Psychometric properties of the critical thinking disposition scale in Peruvian adolescents - Hilda Martínez-Huamán; Josué Edison Turpo-Chaparro; Carlos D. Abanto-Ramírez (Frontiers in Education)
BackgroundThe disposition to critical thinking equips students with the capacity for objective analysis, informed decision-making, and problem-solving. Furthermore, it enhances intellectual autonomy and adaptability within academic contexts.ObjectivesTo assess the psychometric properties of the Critical Thinking Disposition Scale in Peruvian adolescents.MethodologyThe psychometric adaptation process was implemented to evaluate the relevance, clarity, and comprehension of the items through expert judgment and pilot testing. Utilizing a sample of 499 students aged 10–17 years (M = 15.8, SD = 1.30), a confirmatory factor analysis (CFA) was conducted.ResultsThe scale demonstrated validity and reliability, yielding optimal fit and reliability indices that support its unidimensional structure.ConclusionThe validation of the Critical Thinking Disposition Scale in the Peruvian context provides a valuable instrument for assessing and fostering the propensity of Peruvian students to employ critical thinking skills, with implications for professional practice and educational policy. Furthermore, the study is significant because it shows that all factor values were greater than 0.40, which represents that the items contribute significantly to the evaluation of adolescents’ disposition to critical thinking.